Elevated amino acid biosynthesis in Phytophthora infestans during appressorium formation and potato infection - Grenville-Briggs, L.J.; Avrova, A.O.; Bruce, C.R.; Williams, A.; Whisson, S.C.; Birch, P.R.J.; Van West, P.
Appressorium formation is believed to be an important event in establishing a successful interaction between the late blight pathogen, Phytophthora infestans, and its host plants potato and tomato. An understanding of molecular events occurring in appressorium development could suggest new strategies for controlling late blight. We used parallel studies of the transcriptome and proteome to identify genes and proteins that are up-regulated in germinating cysts developing appressoria. As a result, Wve distinct genes involved in amino acid biosynthesis were identiWed that show increased expression in germinating cysts with appressoria. These are a methionine synthase (Pi-met1), a ketol-acid reductoisomerase (Pi-kari1), a tryptophan synthase (Pi-trp1), an acetolactate synthase (Pi-als1), and a threonine synthase (Pi-ts1). Four of these P. infestans genes were also up-regulated, although to lower levels, during the early, biotrophic phase of the interaction in potato and all Wve were considerably up-regulated during the transition(48 hpi)to the necrotrophic phase of the interaction. Real-time RT-PCR revealed that expression of potato homologues of the amino acid biosynthesis genes increased during biotrophic and necrotrophic infection phases. Furthermore, we investigated levels of free amino acids in the pre-infection stages and found that in most cases there was a decrease in free amino acids in zoospores and germinating cysts, relative to sporangia, followed by a sharp increase in germinating cysts with appressoria. Amino acid biosynthesis would appear to be important for pathogenicity in P. infestans, providing a potential metabolic target for chemical control.
Keywords: PROTEOMICS; SSH; REAL-TIME RT-PCR; OOMYCETE; LATE BLIGHT; AMINO ACID BIOSYNTHESIS; PATHOGENICITY